Analisis Perbandingan Perkerasan Kaku dan Perkerasan Lentur Pada Proyek Peningkatan Jalan Celukan Bawang-Pelabuhan - I Ketut Sutapa; Ida Bagus Wirahaji; I Made Gita Ariadi (Universitas Pendidikan Nasional, 2022)
Road pavement is a layer structure located above the subgrade, there is a layer of upper foundation and sub-base which each layer consists of compacted aggregates which have a function to transmit stress due to wheel load. There are 3 road pavements, asphalt or flexible pavement, concrete/ rigid pavement (rigid pavement) and composite pavement (Composit pavement). In determining pavement thickness there are several methods to use, including in this study using the 1993 AASHTO method for flexible pavements and the 2017 Road Pavement Manual method (Bina Marga 2017) for rigid pavements. The location of this research is located on Jalan Celukan Bawang – Pelabuhan, Kec. Gerokgak, Kab. Buleleng. This final project aims to determine the comparison of flexible pavement thickness using the 1993 AASHTO method compared to rigid pavement using the 2017 Highways method and the comparison of implementation costs and maintenance costs on flexible0pavement0and rigid pavement0with0a design life of 10 years. From the results of calculations that have been carried out, the 1993 AASHTO method produces a total thickness of 61 cm with an implementation cost of Rp. 2.363.603.825,33 and maintenance costs of Rp 118.180.191,27, and the 2017 Road Pavement Manual method produces a total thickness of 54.5 cm with an implementation cost of Rp.5.230.581.646,07 and maintenance costs of Rp. 261.529.082,30. From the results obtained, flexible pavement using the 1993 AASHTO method has agreate thickness with lower implementation and maintenance costs than rigid pavement using the 2017 Road Pavement Manual method.